2009
DOI: 10.3201/eid1504.081378
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Leprosy in the Amazon Region of Brazil

Abstract: To detect areas with increased case-detection rates, we used spatial scan statistics to identify 5 of 10 clusters of leprosy in the Amazon region of Brazil. Despite increasing economic development, population growth, and road infrastructure, leprosy is endemic to this region, which is a source of case exportation to other parts of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 3 publications
7
56
0
13
Order By: Relevance
“…In t h e a n a l y s e s b y municipalities, three studies examined the N CDR of the country at different moments in time 10,16,17 , and showed concentration in the North and Midwest regions, and in the Northeastern states located in Legal Amazon. The study by Freitas et al 17 To homogenize results, we described NCDR for 100,000 inhabitants and CP for 10,000 inhabitants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In t h e a n a l y s e s b y municipalities, three studies examined the N CDR of the country at different moments in time 10,16,17 , and showed concentration in the North and Midwest regions, and in the Northeastern states located in Legal Amazon. The study by Freitas et al 17 To homogenize results, we described NCDR for 100,000 inhabitants and CP for 10,000 inhabitants.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1, Table 2 and Table 3 show the articles' summaries according to the scale used: two evaluated regions/ mesoregions 14,15 ; 13 used the scale of municipalities 10,[16][17][18][19][20][21][22][23][24][25][26][27] ; 4 evaluated districts [28][29][30][31] ; 6 studied neighborhoods [32][33][34][35][36][37] ; 7 analyzed the census tracts [38][39][40][41][42][43][44] ; and 3 investigated households [45][46][47] . Within each scale, the articles were organized by location: Brazil, Northern, Northeast, Midwest, and Southeast regions.…”
Section: Resultsmentioning
confidence: 99%
“…1 illustrates their geographic locations. The PA counties were selected based on their geographic position to sample all of the regions of the state and to accommodate PA's leprosy clusters 1 and 7, as identified by Penna et al (2009).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The conglomerate in the northern region of the state is part of cluster 4 of the Health Ministry, together with towns in the southern part of Bahia and the northeastern part of Minas Gerais 18 . The northern macro-region of the state is classified as a hyper-endemic region, confirming its priority condition for programs to control the disease in this state.…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 99%